Blocked by Neoliberalism: A Glance at the Workers Movement’s Role in Achieving a Just Transition - Syahwal, Syahwal (Indonesian Journal of Advocacy and Legal Services, 2024)
An effort to protect workers throughout an economic transition to a sustainable economy gave rise to the concept of a just transition. This is because the transition will have an effect on the employment in which workers are engaged. Based on this concept, this study examines Indonesia’s worker response to a just transition. Non-doctrinal research was used to conduct the study. This study shows that the question of a just transition is not now at the forefront of the workers movement in Indonesia. Neoliberalization of Indonesian labour law, nollen vollens, encourages the workers movement to continue concentrating on economic concerns, particularly those involving the fundamental rights of workers. Under these circumstances, Indonesia runs the risk of failing to accomplish a just transition, which would put workers in a ‘dark world’ while the economy moves towards a green economy.